Defending the Nation in the Cyber Era: Indonesia’s Response to Non Military Security Threats - Rudiyanto, Rudiyanto; Prayitno, Arief (International Journal Labs, 2025)
The rapid development of information and communication technology has brought Indonesia into a complex era of digital transformation. On the other hand, this advancement has also given rise to new challenges in the form of non-military cyber threats that pose significant risks to national stability. This research aims to examine the forms and characteristics of non-military threats in cyberspace and to analyze the effectiveness of Indonesia’s national defense strategies in responding to these threats. The research employs a descriptive qualitative method with a literature study approach. The findings indicate that although the government has established the Badan Siber dan Sandi Negara (BSSN) and issued various regulations, such as Law No. 27 of 2022 on Personal Data Protection and Minister of Defense Regulation No. 82 of 2014, the strategies implemented have not been fully effective. This is due to weak interagency coordination, limited human resources, and suboptimal law enforcement. Therefore, strengthening governance, improving digital literacy, and fostering cross-sector collaboration are essential to building a resilient national cyber defense system.